Assessment of dietary intake and sociodemographic status of patients with lung cancer - Zabłocka, Katarzyna; Gołecki, Marcin; Ilow, Rafał; Porębska, Irena; Kosacka, Monika; Bzdok, Magdalena; Rzechonek, Adam; Kamińska, Aleksandra; Jankowska, Renata; Biernat, Jadwiga (Contemporary Oncology/Współczesna Onkologia, 2011)
The aim of this paper was to assess dietary intake and characterize the sociodemographic and smoking status in a lung cancer patient group. Material and methods : The research was performed among 15 women and 29 men who carried out a questionnaire of sociodemographic status and 24-h dietary recall from the last three days before hospitalisation. Obtained results were compared with Polish RDA (Recommended Dietary Allowances) and references. Results : Every third person of all respondents had a vocational education; a similar percentage of patients were primary educated. All subjects were current or former smokers. Intake of fat and saturated fatty acids was higher than RDA and there were found deficiencies of polyunsaturated fatty acids and carbohydrates. The average diet of men and women provides copper and zinc below the relevant RDA. Only the average mean daily supply of sodium and phosphorus in meals of patients exceeded RDA of these minerals. The mean intake of antioxidant vitamins with diets was too high while the mean amount of B group vitamins in diets was lower than RDA. Conclusion : Incorrect dietary habits demonstrated in patients during the period before lung cancer diagnosis in combination with smoking and low education could contribute to the development of lung cancer.